2020
DOI: 10.1038/s41598-020-71067-x
|View full text |Cite
|
Sign up to set email alerts
|

Towards applying NMR relaxometry as a diagnostic tool for bone and soft tissue sarcomas: a pilot study

Abstract: This work explores what Fast Field-Cycling Nuclear Magnetic Resonance (FFC-NMR) relaxometry brings for the study of sarcoma to guide future in vivo analyses of patients. We present the results of an ex vivo pilot study involving 10 cases of biopsy-proven sarcoma and we propose a quantitative method to analyse 1 H NMR relaxation dispersion profiles based on a model-free approach describing the main dynamical processes in the tissues and assessing the amplitude of the Quadrupole Relaxation Enhancement effects du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…On the other hand, our group has recently demonstrated that measuring T 1 at lower magnetic field strengths can be very informative and report on the tumor metabolic status (10,11). This is possible because tissue T 1 varies with applied magnetic field strength, with the differences between tissues being higher at lower magnetic field strengths (12)(13)(14)(15). This behavior (often referred to as "T 1 -dispersion", or simply relaxometry) is a marker of disease, but is invisible to conventional, fixed-field MRI scanners.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, our group has recently demonstrated that measuring T 1 at lower magnetic field strengths can be very informative and report on the tumor metabolic status (10,11). This is possible because tissue T 1 varies with applied magnetic field strength, with the differences between tissues being higher at lower magnetic field strengths (12)(13)(14)(15). This behavior (often referred to as "T 1 -dispersion", or simply relaxometry) is a marker of disease, but is invisible to conventional, fixed-field MRI scanners.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, administration of dasatinib and FAK inhibitor 14 resulted in a reshaped metabolic profile both in normal fibroblasts and in desmoid tumor cells, with the cell line differentiation process being led by aminoacyl-tRNA biosynthesis in mitochondria and cytoplasm, as well as by signal transduction amino acid-dependent mTORC1 activation [ 51 ]. Masiewicz et al developed an innovative approach, employing Fast Field-Cycling, an NMR technique that measures spin-lattice relaxation rates over a wide range of magnetic fields, and that, even not being a classic metabolomic approach, provides an extraordinary insight on the molecular dynamics of the modifications of intra and extra-cellular compartments of tumor cells imposed by pathological changes in sarcomas [ 52 ]. The authors investigated spin-lattice relaxation properties of sarcoma using formaldehyde-fixed resections from surgery and analyzed the differences in the spin-lattice relaxation dispersion profiles of musculoskeletal malignancies, tissues adjacent to the tumor, and apparently healthy tissues obtained at the resection margin, with the goal of improving the diagnostic accuracy of musculoskeletal malignancies [ 52 ].…”
Section: Techniques and Approaches Used For Soft Tissue Sarcomas Meta...mentioning
confidence: 99%
“…The herein reported results show that an approach based on nuclear magnetic resonance (NMR) relaxometry may allow tumour margin assessment on excised tissue specimens without the need for spatial discrimination (i.e., without imaging). It is well known that proton T 1 values of a given tissue decrease as a function of the applied magnetic field strength, thus providing larger differences among the tissues the lower the applied magnetic field strength is [29][30][31]. This behaviour, known as T 1 -dispersion, is closely linked to the mechanisms that drive molecular dynamics within the sample and can therefore be exploited in the search for novel diagnostic markers.…”
Section: Introductionmentioning
confidence: 99%